184k views
5 votes
Use completing the square to solve the equation x2 - 10x = -8.

Which equation is used in the process?

x2 - 10x + 25 = 17
x2 - 10x + 25 = -8
x2 - 10x - 25 = -33

User De Novo
by
5.9k points

2 Answers

4 votes

Answer:

number one!!

is your answer!!

User HolyBlackCat
by
5.9k points
7 votes

Answer:

x^2 - 10x + 25 = 17

Explanation:

Please use " ^ " to denote exponentation:

x^2 - 10x = -8

x^2 - 10x + 25 = 17

x^2 - 10x + 25 = -8

x^2 - 10x - 25 = -33

Begin with x^2 - 10x = -8. Here's the process for completing the square:

1. Take half of the coefficient of x and square the result:

(1/2)(-10) = -5, and then (-5)^2 = + 25

2. Add this 25 to the first two terms of x^2 - 10x = -8 and also to the constant -8: x^2 - 10x + 25 = -8 + 25, or x^2 - 10x + 25 = 17

3. Match this result to one of the given possible answers. Turns out that the given possible answer matching our result is the first one:

x^2 - 10x + 25 = 17

User Illya Bublyk
by
6.3k points